Diagnosis of acute toxoplasmosis by an enzyme immunoassay for specific immunoglobulin m antibodies. - Wielaard, F (1983)
A recently developed enzyme-linked immunosorbent assay for detection of immunoglobulin M (IgM) class antibodies to Toxoplasma gondii was evaluated with respect to specificity and sensitivity. By using an antibody capture principle and F(ab')2 conjugates, interference of rheumatoid factors was absent. No cross-reactions with anti-toxoplasma IgG occurred, and no interference with antinuclear antibodies was found. A large-scale study with about 1,500 clinical specimens revealed a 100% specificity. By testing 79 sera from patients with acute-phase acquired toxoplasmosis, sensitivity was found to be 97%. In routine clinical practice, the IgM-enzyme-linked immunosorbent assay proved to be a more sensitive tool for diagnosis than the immunofluorescent-antibody test. The course of IgM-enzyme-linked immunosorbent assay antibodies in acute patients was studied; IgM reached peak levels within 1 month after onset of illness, and could be demonstrated up to an average of 8 months after onset.